China's Arctic geostrategies in political and economic processes - DIKARIEV O.I.; SHOSTAK L.B. (Zenodo, 2019)
The subject of the study political and economic strategies for the distribution and use of natural resources by the Arctic countries. The purpose of the article – author’s vision of the benefits of the arctic strategy of China and promising directions of Ukraine’s participation in solving the strategic tasks of sustainable development of the region. Methodology of the work general macroeconomics, theories of sectoral markets and sustainable development. On the basis of the system approach, factors influencing the sustainable development of the Arctic region are identified. Using the methods of expert analysis, the main directions of the Chinese geopolitical strategy are determined. Structure and synthesis methods reveal the strengths and weaknesses of international cooperation in the joint use of natural resources in the Arctic. on three main topics: (1) the first is the growing circumpolar collaboration between organizations of peoples and regional governments: the North meets the North, (2) region–building under paramount participation of states with a focus on the Arctic Council, (3) the relationship of the Arctic with the outside world, (4) effects non–system actors (China) on the transformation of geopolitical and geo–economic strategies in the Arctic region as the sixth part of world space north of the parallel 66 ° 33’39» with a population of 4 million people in eight circumpolar countries: Canada, Denmark (Greenland), Finland, Iceland, Norway, Russia, Sweden and the United States, rich in renewable (fish, sea animals) and non– renewable resources (up to 20% of world mineral reserves), (5) influence of ice melting on geopolitical and geo–economical situation in Arctic; «Polar Silk Road», White Paper «China’s Arctic Policy» China justifies its role in the fight against global warming and the need to participate in the development of decisions regarding the Arctic as a whole. Beijing’s interests are not limited to shipping and the development of mineral resources of the bottom and subsoil, they are also ...